Karla's choice : a John le Carré novel - Harkaway, Nick, 1972- (Viking, 2024)
"An extraordinary new novel set in the world of John le Carré's most iconic spy, George Smiley, written by acclaimed novelist Nick Harkaway. It is spring in 1963 and George Smiley has left the Circus. With the wreckage of the West's spy war against the Soviets strewn across Europe, he has eyes only for a more peaceful life. And indeed, with his marriage more secure than ever, there is a rumor that George Smiley might almost be happy. But Control has other plans. A Russian agent has defected in the most unusual of circumstances, and the man he was sent to kill in London is nowhere to be found. Smiley reluctantly agrees to one last simple task: interview Szusanna, a Hungarian émigré and employee of the missing man, and sniff out a lead. But in his absence, the shadows of Moscow have lengthened. Smiley soon finds himself entangled in a perilous mystery that will define the battles to come and set him on a collision course with the greatest enemy he will ever make. Set in the missing decade between two iconic instalments in John le Carré's George Smiley saga, The Spy Who Came in from the Cold and Tinker Tailor Soldier Spy, Karla's Choice marks a momentous return to the world of spy fiction's greatest writer"--